Indonesia Representasi Feminisme dalam Drama Netflix “The Glory Season 1” (Analisis Semiotika John Fiske) - Safitri, Dewi (Jurnal Public Relations (J-PR), 2023)
Mass media is an important tool for society to communicate and convey information. Mass media influence human attitudes and behavior, and have educational, influential, informational, and entertainment functions. Drama is a form of mass media that can raise social issues, including gender equality. Feminism is a movement that fights for gender equality, and drama often reflects feminist views. Korean dramas, such as K-Dramas, are very popular and often raise the issue of bullying and domestic violence, especially against women. Some dramas portray women as figures who only focus on their appearance, while others feature strong and brave women like Moon Dong-eun's character in "The Glory Season 1." "The Glory Season 1" is a drama that raises important issues related to feminism and women's representation. The drama highlights the unfair treatment experienced by women and features Moon Dong-eun's character as the embodiment of strong and courageous women. In this study, using descriptive qualitative research methods with an ethnographic approach and semiotic analysis of John Fiske. The results showed that this film illustrates the importance of justice, courage, and the active role of women in achieving gender equality. In conclusion, the film "The Glory Season 1" shows an inspiring feminist narrative and emphasizes the important role of women in changing fate and getting equal treatment. Keywords : Feminism, John Fiske's Semiotics, The Glory Season 1